Integrating Islamic principles in community mental health services - Abdullah, Kartini; Mat Zin, Nora; Md Rosli, Najwa Hanim; Md Tahir, Mohd Faiz; Mohd Noor, Hanisah; Musa, Ramli (2016)
Mental health services in most of the countries have shifted from traditional custodial care in the hospital to the community based treatment. In Malaysia, the services have started many years ago and have achieved several milestones. One of the components of community mental health services are home based treatment and psychosocial intervention. Social assessment is more precise when patients are seen on their turf. Effective treatment strategies can be planned based on the individual social circumstances. Other than its cost effectiveness as compared to hospitalisation rate (Simmonds et al, 2001), (R Dahlan, M Midin, H Sidi, T Maniam, 2013), home based treatment caters patients at all range of ages from infanthood to elderly. Reducing stigma towards mental illness is another goal for these services. However, the most challenging part lies in its unique setting and boundaries which needs flexible approach. The religion of Islam has strongly emphasized the importance of visiting the sick or ‘iyaadah’ as supported by several hadeeths. It has complete etiquettes that would be the best guideline when integrating Islamic values in home based therapy that will be highlighted in this paper. When Malaysia is largely populated by Muslim, it is worth to work on it. The issues of boundaries and stigma encountered when handling patients with mental illness during home care treatment will be further discussed in the context of maqasid syariah.